2004
DOI: 10.1111/j.1442-9071.2004.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of relative contribution of the superior and inferior canaliculi to the lacrimal drainage system in health using the drop test

Abstract: The drop test was found to provide a simple and repeatable method of assessing lacrimal drainage in a minimally invasive manner in the clinical setting. In healthy volunteers in the supine position 60% of maximal lacrimal outflow capacity occurs through the inferior canaliculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…For the normal drainage, tears are mainly drained through the lower canaliculus, 16 however, when the ocular fluid volume is significantly larger than normal, as for instillation, the upper canaliculus also contributes to drainage. 17 Therefore, for the case of extra fluid instillation, the term corresponding to the drainage rate through the canaliculi in Eq. (3) should be multiplied by a factor, the value of which is between 1 and 2, depending on the fluid volume remaining on the ocular surface.…”
Section: Dynamic Tear Balancementioning
confidence: 99%
“…For the normal drainage, tears are mainly drained through the lower canaliculus, 16 however, when the ocular fluid volume is significantly larger than normal, as for instillation, the upper canaliculus also contributes to drainage. 17 Therefore, for the case of extra fluid instillation, the term corresponding to the drainage rate through the canaliculi in Eq. (3) should be multiplied by a factor, the value of which is between 1 and 2, depending on the fluid volume remaining on the ocular surface.…”
Section: Dynamic Tear Balancementioning
confidence: 99%
“…Tears are moved into the lacrimal puncta by negative pressure created within the lacrimal drainage system during a blink 42 . The majority of tears drain through the lower puncta; 43,44 however, if drainage is impaired in the lower puncta, sufficient drainage can be obtained through the upper puncta 42,45,46 . Finally, tears move via gravity from the upper tear meniscus to the lower one.…”
Section: Tear Film Dynamicsmentioning
confidence: 99%
“…It is therefore difficult to determine whether repair of the lacerated or avulsed canaliculus is providing a functioning system. A previous study calculated, using the drop test, that the maximal outflow capacity does reduce if one punctum is occluded; however, this level is still much higher than normal basal tear production 5 . Murgatroyd et al .…”
Section: Discussionmentioning
confidence: 96%
“…A previous study calculated, using the drop test, that the maximal outflow capacity does reduce if one punctum is occluded; however, this level is still much higher than normal basal tear production. 5 Murgatroyd et al suggest that the capacity of the common canaliculus may limit flow along two patent canaliculi, thus allowing increased flow along a patent canaliculi when the other is occluded. 5 Because of this, some authors have advocated not repairing a monocanalicular injury; a survey of UK consultants with an oculoplastics' interest reported that only 40% would always repair a moncanalicular injury.…”
Section: Discussionmentioning
confidence: 99%